Political legitimacy - Knight, Jack, 1952-; Schwartzberg, Melissa, 1975- (Nomos ;, 2019)
Scholars, journalists, and politicians today worry that the world's democracies are facing a crisis of legitimacy. Although there are key challenges facing democracy--including concerns about electoral interference, adherence to the rule of law, and the freedom of the press--it is not clear that these difficulties threaten political legitimacy. Such ambiguity derives in part from the contested nature of the concept of legitimacy, and from disagreements over how to measure it. This volume reflects the cutting edge of responses to these perennial questions, drawing, in the distinctive NOMOS fashion, from political science, philosophy, and law--back cover.